ADAB MEMINTA IZIN DALAM PERSPEKTIF AL-QUR’AN: ANALISIS TAFSIR QS. AN-N?R AYAT 27–29 SEBAGAI FONDASI ETIKA SOSIAL ISLAM - Isnan Ansory; Athifah Muthiatunnisa (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
The Qur’an, as the primary source of Islamic teachings, does not only regulate theological and ritual aspects but also provides comprehensive guidance on social ethics aimed at establishing a civilized and dignified social order. One such ethical regulation is the teaching of seeking permission before entering another person’s house, as explicitly stated in Q. an-N?r (24): 27–29. This article aims to analyze the concept of seeking permission (adab al-isti’dh?n) from the Qur’anic perspective, classical and contemporary exegetical interpretations, and its relevance to the development of Islamic social ethics. This study employs a library research method with a descriptive-analytical approach and the tahl?l? method of Qur’anic exegesis. Primary data sources include the Qur’an and classical as well as contemporary tafs?r works, while secondary sources consist of scholarly books and relevant academic journal articles. The findings indicate that seeking permission constitutes a preventive ethical system in Islam that functions to protect human dignity, privacy, and social order. This ethical injunction not only regulates interpersonal relations but also reflects the integration of moral, spiritual, and social values within Islamic teachings. Therefore, the ethics of seeking permission retains strong normative and contextual relevance in modern society as an instrument for shaping social morality grounded in Qur’anic values.